Spatial Heterogeneity and Temporal Stability of Baseflow Stream Chemistry in an Urban Watershed - Claire Welty; Joel Moore; Daniel J. Bain; Mahdad Talebpour; John T. Kemper; Peter M. Groffman; Jonathan M. Duncan (Water Resources Research, 2023)
Abstract Synoptic sampling of streams is an inexpensive way to gain insight into the spatial distribution of dissolved constituents in the subsurface critical zone. Few spatial synoptics have focused on urban watersheds although this approach is useful in urban areas where monitoring wells are uncommon. Baseflow stream sampling was used to quantify spatial variability of water chemistry in a highly developed Piedmont watershed in suburban Baltimore, MD having no permitted point discharges. Six synoptic surveys were conducted from 2014 to 2016 after an average of 10 days of no rain, when stream discharge was composed of baseflow from groundwater. Samples collected every 50 m over 5 km were analyzed for nitrate, sulfate, chloride, fluoride, and water stable isotopes. Longitudinal spatial patterns differed across constituents for each survey, but the pattern for each constituent varied little across synoptics. Results suggest a spatially heterogeneous, three‐dimensional pattern of localized groundwater contaminant zones steadily contributing solutes to the stream network, where high concentrations result from current and legacy land use practices. By contrast, observations from 35 point piezometers indicate that sparse groundwater measurements are not a good predictor of baseflow stream chemistry in this geologic setting. Cross‐covariance analysis of stream solute concentrations with groundwater model/backward particle tracking results suggest that spatial changes in base‐flow solute concentrations are associated with urban features such as impervious surface area, fill, and leaking potable water and sanitary sewer pipes. Predicted subsurface residence times suggest that legacy solute sources drive baseflow stream chemistry in the urban critical zone.